Wangque de Yitian . A Day to Remember - Wei, Liu (Liu, Wei, 2005)
Verzio FF It is 4 June 2005. The cineaste Liu Wei picks up his camera and sets off for Tiananmen Square and the University of Beijing with a question in his head: what day is it? As he poses this question to the various students and people that he encounters on his way, he receives countless evasive replies and the refusal of majority to recall the student protests 16 years earlier. Many affirm that they not know anything about those events and move swiftly onwards while others only stare at the camera. A Day to Remember reflects the great unease surrounding the date of 4 June and how the uprising of that period still remains taboo subject in the People’s Republic of China. Nevertheless, this film by Liu breaks with that silence and explores an entire nation’s feelings of denial.